2016
DOI: 10.18287/jbpe16.02.010307
|View full text |Cite
|
Sign up to set email alerts
|

Craquelure structure of protein film modification under the laser radiation of different spectral range action

Abstract: Abstract.A craquelure structure of protein film as indicator of macromolecule state is discussing. Craquelure is a network of fine cracks or crackles on the surface of a painting, caused chiefly by shrinkage of paint film or varnish. The actions of laser radiation in the red and green spectral region on the protein film craquelure structure by the example of albumin are considering. It is experimentally shown that after drying the protein layer a craquelure pattern (variety of cracks in the layer) is formed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In Refs. [6][7][8][9][10] it is shown that in relation to the protein and bile solutions this statement finds its experimental confirmation.…”
Section: Introductionmentioning
confidence: 94%
“…In Refs. [6][7][8][9][10] it is shown that in relation to the protein and bile solutions this statement finds its experimental confirmation.…”
Section: Introductionmentioning
confidence: 94%
“…The effect of laser radiation on protein solutions was studied in Ref. [9]. It was shown that as a result of the exposure of protein solution to laser radiation the craquelure structure (rupture pattern) of its dried film is changed.…”
Section: Introductionmentioning
confidence: 99%